Lamellar Keratoplasty: A Literature Review - Ladan Espandar; Alan N. Carlson (Journal of Ophthalmology)
The concept of lamellar keratoplasty (LK) is not new. However, newer forms of lamellar keratoplasty techniques have emerged in the last decade or so revolving around the concept of targeted replacement of diseased corneal layers. These include anterior lamellar keratoplasty (ALK) techniques that aim to selectively replace diseased corneal stroma and endothelial keratoplasty techniques aiming to replaced damaged endothelium in endothelial disorders. Recent improvements in surgical instruments and introduction of new techniques as well as inherent advantages such as preservation of globe integrity and decreased graft rejection have resulted in the reintroduction of LK as an acceptable alternative to conventional PK. In this review, indications, benefits, limitations, and outcomes of various anterior and posterior lamellar keratoplasty techniques are discussed.